Profil Komunitas Hutan Pendidikan Gunung Walat, Jawa Barat - Firman Ali Rahman; Taufik Arianto; Sulistijorini; Anis Syakiratur Rizki; Mai Rizali (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2024)
The vegetation profile is a vertical and horizontal description as well as the structure and species composition of a vegetation which includes the dominance of canopy cover, species diversity, species dominance, species frequency, species density and undergrowth. This research aims to obtain an overview of the composition, vertical and horizontal structure of vegetation so as to provide information about tree dynamics and ecological conditions as well as to view tree architectural models. The method for collecting community profile data is carried out in each sample plot measuring 20x20 m with data requirements such as: trunk diameter at DBH height, tree height, tree height, canopy limit, and tree canopy projection. Based on data on tree height and diameter, it was concluded that the trees in the research plot area were trees of the past because they had a total height of between 20-54 meters with a trunk diameter of ±1.63 meters. the results of drawing architectural profiles of tree canopy projections horizontally and vertically so that we can see models of canopy closure and competition for sunlight in homogeneous forest tree communities consisting of the Agathis loranthifolia species. The results of the horizontal and vertical projection of the architectural profile of the tree canopy can be seen so that the model of canopy closure and competition for sunlight in a homogeneous forest tree community consisting of the Agathis loranthifolia species can be seen. The ecological function of the Agathis loranthifolia type is very good in maintaining the environment, related to groundwater storage which can reduce the impact of soil erosion rates. Certain tree architectural models influence the transformation of rainwater into stem flow rate, water through the canopy, infiltration and surface flow rate in an area which is related to the role of vegetation as disaster mitigation.